(3fXe EOGQI bhGYO GdHjGfGJs - (3SYO ZGdH(B, (3jGSjfs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3eaGgje bGYOI GdHjGfGJ(B- (3YedjI JWhjQ bGYOI GdHjGfGJ(B- (3GdfehPL GdYdGFbj dbGYOI GdHjGfGJ(B- (3fehPL GdcjfhfI hGdYdGbGJ GdeWhQ hbhGYO GdCYeGd(B- (3GdJUeje GdefWbj dbGYOI GdHjGfGJ(B- (3GdJWHjY hGdYdGbGJ GdeYjGQjI(B- (3dZI GdESJYdGe GdHfjhjI(B- (3bhGYO GdHjGfGJ GdehLgI ddcjfhfGJ(B.s
(3eQGLY U(B.319 (3;GdaUd GdYGTQ YHGQI Yf GSFdI h GLhHI HGddZI GdGfLdjRjI U(B.261s
Keywords: (3GdEOGQIs; (3GdeYdheGJs; (3bhGYO GdHjGfGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s